Does Daylight Saving Time Really Make Us Sick? - Lawrence Jin; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2015)
This paper comprehensively studies the health effects of Daylight Saving Time (DST) regulation. Relying on up to 3.4 million BRFSS respondents from the US and the universe of 160 million hospital admissions from Germany over one decade, we do not find much evidence that population health significantly decreases when clocks are set forth by one hour in spring. However, when clocks are set back by one hour in fall, effectively extending sleep duration for the sleep deprived by one hour, population health slightly improves for about four days. The most likely explanation for the asymmetric effects are behavioral adjustments by marginal people in spring.
Keywords: H41; I18; I31; 330; Daylight Saving Time (DST); BRFSS; hospital admissions; sleep deprivation; Germany; US